Degloving injury of ascending colon following blunt abdominal trauma - Tharveen N.; Andre D.; Firdaus O.; Hayati F.; Affirul C.A. (Krishna Institute of Medical Sciences University, 2024)
Degloving injury to the colon caused by blunt abdominal trauma is an extremely rare injury. To our knowledge, this is the first reported case of degloving injury to the ascending colon in the literature which further accentuates the rarity of this case report. This is a 40-year-old gentleman who was a motorcyclist, had a road traffic incident where he was hit by a car from the back. On arrival, he was hemodynamically stable but there was tenderness over right side of the abdomen. Computed Tomography (CT) of the abdomen showed large ascending colon haematoma with contrast extravasation. An emergency laparotomy revealed a degloving injury of the ascending colon and the mesentery thus, a right hemicolectomy was performed. The postoperative course was uneventful and patient was discharged well. We describe a 40-year-old gentleman who had involved in road traffic accident, sustained degloving injury to the ascending colon and discuss its literature review. Journal of Krishna Institute of Medical Sciences University.